Studi Kasus Keperawatan Terapi Bercerita pada Pasien Skizofrenia Rawat Jalan dengan Risiko Perilaku Kekerasan - Hikmawati, Hikmawati; Razak, Rasniati; Wijayati, Fitri (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2025)
Schizophrenia is a severe and systemic brain disorder that causes disturbances in psychotic behavior, concrete thinking, information processing, interpersonal relationships, and problem-solving abilities. Individuals with a risk of violent behavior are those who have the potential to harm themselves, others, or the environment physically, emotionally, sexually, or verbally due to an inability to control anger in a constructive manner. This nursing care aimed to apply storytelling therapy to improve self-control in patients with a risk of violent behavior at the UPTD Community Health Center of South Lasalimu District, Buton Regency. This study employed a descriptive case study design involving one outpatient schizophrenia patient with the primary nursing problem of risk of violent behavior who received storytelling therapy. The results of the case study demonstrated that the implementation of storytelling therapy contributed to an improvement in the patient’s self-control, as indicated by a reduction in the self-control score from 4 to 1. Self-control improvement in patient Tn. A was achieved through the provision of storytelling therapy conducted over 12 sessions. Based on the findings of this case study, it is recommended that nurses apply storytelling therapy as part of psychiatric nursing care for patients with a risk of violent behavior. Contribution to the Sustainable Development Goals (SDGs) This case study examines the application of storytelling therapy as a nonpharmacological nursing intervention to improve self-control in outpatient schizophrenia patients with a risk of violent behavior. The article contributes to Sustainable Development Goal (SDG) 3: Ensure healthy lives and promote well-being for all at all ages. Specifically, it supports Target 3.4, which aims to promote mental health and well-being through effective prevention and treatment strategies for mental disorders. By highlighting the role of therapeutic communication and psychosocial nursing interventions in managing violent behavior risk, this study underscores the importance of accessible, community-based mental health care in improving patient outcomes and overall well-being.